A taxonomic study on Orthoprotella and related genera (Crustacea: Amphipoda: Caprellidae) of New South Wales, Australia. Issue 17 (11th May 2019) - Takeuchi, Ichiro; Lowry, James K.
ABSTRACT: The present study reviews the taxonomy of Orthoprotella, Metaprotella and Notoprotella gen. nov. (Crustacea: Amphipoda: Caprellidae) from the coast of New South Wales, Australia. In total eight species from these genera are recorded from the New South Wales coasts. Generic diagnoses of Orthoprotella, Metaprotella and Notoprotella gen. nov. are provided based on the present materials with recent detailed descriptions. The following five species are described in detail: Metaprotella guileri sp. nov., M. solitaria sp. nov., Notoprotella cornuta gen. nov., sp. nov., Notoprotella gordoni, new combination, and Orthoprotella australis. Metaprotella guileri sp. nov. is close to M. excentrica, but differs in pereonite 2 lacking a pair of pfosterior dorsal projections and lacking three distal small projections on the basis of gnathopod 2. Metaprotella solitaria sp. nov. is close to M. guileri sp. nov. and M. haswelliana, but differs from these species by the difference of projection formation of pereonites 2 to 3. Notoprotella cornuta gen. nov., sp. nov. is close to Notoprotella berentsae, but differs in having a mid-lateral projection near the base of gnathopod 2 and a distinct middorsal projection on pereonite 2. http://www.zoobank.org/urn:lsid:zoobank.org:pub:7E38CE67-297F-4187-A1DF-A2F3EAEC51D4